Activation of B1 B cells by F. tularensis atypical LPS depends on classical complement and C3a - Melo, Guilherme; Barbosa, Carlos Henrique D.; Magrini, Elena; Garlanda, Cecilia; Re, Fabio (PLOS Pathogens, 2025)
Francisella tularensis (Ft), a Gram-negative bacterium that causes tularemia, possesses a non-inflammatory atypical LPS (LPSFt) that is highly immunogenic through unknown mechanism. We previously showed that immunization with LPSFt, a type 2 T-independent (TI) antigen, elicits protective LPSFt-specific IgM (IgMFt) and IgG3Ft by B1 cells in a mechanism dependent on the IL-5 produced by innate lymphoid cells type 2 (ILC2). Here, we examined the role of complement in the B1 cells’ response against LPSFt. C3-/-, C1q-/- and C4-/- mice immunized with LPSFt failed to produce IgMFt and IgG3Ft. In contrast, the response of Cfb-/- and Mbl1/Mbl2-/- mice was comparable to that of WT mice. Thus, activation of the classical complement cascade, but not the alternative or the Mannose Binding Lectin pathway, is required for activation of B1 cells and production of LPSFt-specific antibodies. Complement activation generates the C3d fragment, which opsonizes antigens for recognition by complement receptor-2 (CR2), and the C3a and C5a anaphylatoxins. Our results show that C3d opsonized LPSFt and that the response to immunization was dependent on CR2 expression by B1 cells. Importantly, the response to LPSFt immunization was also drastically decreased in C3ar1-/-, but not in C5ar1-/- mice. C3a induced IL-5 in ILC2, which supported B1 cells activation. Decreased antibody production in C3ar1-/- and Cr2-/- mice correlated with increased susceptibility to tularemia. Together, these results demonstrate that the high immunogenicity of LPSFt depends on two effector mechanisms triggered by activation of the classical complement pathway: 1) tagging of LPSFt with C3d fragment, leading to its interaction with CR2 expressed by B1 cells; 2) production of the anaphylatoxin C3a that stimulated IL-5 secretion by ILC2. Our study increases our understanding of the B1 cells’ response to TI-2 antigens and identifies two complement effector mechanisms that can be harnessed for therapeutic interventions.